STATESMAN: PRETENSION TO ANALYSIS OF CONCEPT - Jokubaitis, Alvydas; Lopata, Raimundas (Politologija, 2015)
The term statesman has got a positive connotation in Western political vocabularies. The situation in Lithuania is different. Peculiarities of politicalprocess lead to devaluation of the term. During the interwar period in Lithuania the term statesman was more often used by right-wing politicians as a reference designating qualitative evaluation of politicians and other stateagents. Statesman got broader meaning and was used more often by Lithuanian emigrants in the USA. The Renaissance of the term was influenced by Anglo-Saxon political and cultural environment, nostalgia of lost statehood and striving to maintain political identity. In Post-Communist Lithuania thanks to historians the term statesman became one of the instruments in political vocabulary. For some political parties this concept is a tool to achieve political power.There are three conceptions of the term statesman – idealistic, realistand administrative-bureaucratic. Proponents of idealistic conception thinkthat statesman has to establish important political principles for future generations, he has to see further and deeper than other political agents, bevirtuous, just and capable of defending the liberal state. Proponents of thisview think that statesman has to be moral authority. Realist conception ofstatesman is based on different understanding of the relationship betweenmorality and politics. Realists are not advocates of immoral politics, but theythink that some circumstances of political life make it necessary to raise therequirements of the state higher than those of morality. Nicollò Machiavelliformulated the idea that state has got its own autonomous foundations ofexistence which are different from those of morality and religion. He formedthe idea that when there is an exceptional situation, statesman has to look to the interests of state and not those of morality. Henry Taylor is the creatorof administrative-bureaucratic conception of statesman. He is of the opinionthat a man who has mastered the art of implementation of political functionscan make a righteous claim to the title of statesman.